El Ruido 1/f - Betancourt Uscategui, Alvaro (Ingeniería, 1999)
Low frequency fluctuations showing a power spectral density inversely proportional to the frequency are observed in various physical, technical, biological, and economic systems. This is peculiar phenomemon which is called 1/f noise or flickernoise has stimulated the research efforts of numerous scientists since the early work of Johnson [1] and Schotty [2].